Neutrophil-to-lymphocyte ratio predicts a poor prognosis for penile cancer with an immunosuppressive tumor microenvironment - Tan, Xingliang; Wang, Yanjun; Yu, Yiqi; Zheng, Runhao; Li, Jing; Chen, Shaohua; Xie, Qingling; Guo, Shengjie; Zhang, Chichen; Deng, Xinpei; Liu, Zhicheng; Tang, Yi; et al. (Frontiers in Immunology, 2025)
BackgroundChronic inflammation related to poor genital hygiene is a well-recognized pathogenic trigger for penile cancer (PC). The neutrophil-to-lymphocyte ratio (NLR) is a simple, reproducible systemic inflammatory marker and has been reported to indicate unfavorable outcomes. However, previous studies were limited by small sample sizes, confounding prognostic factors and a lack of high-quality evidence demonstrating the significance of the NLR in PC.MethodsA large multicenter cohort of 582 PC patients who underwent radical inguinal lymphadenectomy with definitive pN stage information was assessed. Univariate and multivariate Cox regression analyses were performed to investigate the prognostic value of inflammation-related markers. Propensity score matching (PSM) was used to minimize confounding prognostic clinicopathological features. Immunofluorescence was used to assess the immunosuppressive tumor microenvironment (TME).ResultsA high preoperative NLR (≥ 3.0) was associated with advanced pT, pN, and pathological grade and lymphovascular invasion in PC patients. After PSM to eliminate interference from clinical factors, pN and the NLR were found to be independent prognostic indicators (both p<0.001). PC patients with high NLRs had shorter progression-free survival (PFS) and poorer cisplatin-based chemotherapy and PD-1 immunotherapy response. We also found that the NLR is associated with proinflammatory cytokine secretion and increased N2 tumor-associated neutrophils (TANs) infiltration and CD8+ T-cell exhaustion in TME. N2 TANs induced neutrophil extracellular trap formation might contribute to tumor progression and resistance in high-NLR PC patients.ConclusionsThe NLR is an effective, simple and independent prognostic indicator for PC. A high NLR is associated with an immunosuppressive TME and poor outcomes.